Perancangan Alat Penyaring Otomatis Sari Pati Kedelai pada Pembuatan Tahu untuk mengurangi Waktu Proses dengan Metode Reverse Engineering (Studi Kasus: Rumah Produksi Tahu APU Klaten) - Fauzan, Asepta Gesit; , Ratnanto Fitriadi, ST., MT (2017)
Tahu is one of the favorite food of Indonesian people who can be reached among all because it contains a myriad of benefits one vegetable protein. Competition in the production of Tahuis very rapid, ranging from factories using traditional to modern equipment affect the timing and results of production. The production house Tahu APU(Al-Azhar Peduli Umat) is located in Klaten, Central Java is one of the industry knows that is growing. The equipment used is the traditional combined with modern equipment in some lines such as cooking stoves and milling. The science of knowledge and technology has an important role in various lines of industrial food industry one knows. Evaluation in terms of time in the screening process and production equipment to support the screening process diperluhkan. This research aims to design separator soybean starch with methods Reverse Engineering (RE) to provide an increase in its production process. Making filter tools soy starch refers to several problems such as washing machines dryers, soybean milk maker, and oil drainer on industrial chips. Designing together business owners know it recommends the use of automatic filters soy starch. The results of this research is the design tool automatically filters essence of soy with the motor to speed production tool. This filter tools have the advantage of a faster separation than the separation using traditional ways of soy porridge ease of distribution, excretion of waste products, cleaning, and a number of large production capacity. Production time for manual screening of approximately 5 minutes while separately the tool is only about 3 minutes. Maximum capacity of 46.27 kg of these tools are usually entrepreneurs know only by 10-15 kg in one cooking process .